Baltic Linguistics in Lithuania During a Century - Stundžia, Bonifacas (Lietuvių kalba, 2023)
The article reviews the research of Baltic linguistics, including ancient writing, in Lithuania from the 1920s to the early 21st century. The aim was to discuss the development of some of the more important areas, directions and methods of Baltic linguistics, linking it with changes in public life and conjuncture, as well as national culture, and highlighting significant works. It begins with relatively modest but ambitious pre-war research conducted by traditional philological and comparative historical methods. It goes on to look at the oppressive time of the post-war ideological dictatorship, when, in principle, only activities of a practical nature were possible. The period of the so-called Thaw (ca. 1954–1965) allowed for some fresh air and maturing of the elite of Baltic language researchers, which in the years of stagnation (ca. 1965–1985) mastered the methods of internal reconstruction and structural linguistics, published significant works on the history of language, etymology, onomastics and synchronical linguistics, including theoretical ones, laid the foundations of schools of phonology and word formation. The review concludes with an epoch of Soviet transformation and restored independence (ca. 1985 to the present), which liberated researchers and gradually led to international horizons. Research in applied linguistics, terminology, stylistics, rhetoric and some other directions was discussed by collegues.
Keywords: linguistics; Baltic linguistics; main trends; main methods; development of Baltic linguistics; Old Prussian linguistics; Latvian linguistics